2018
DOI: 10.1177/1049909118804984
|View full text |Cite
|
Sign up to set email alerts
|

Development and Preliminary Evaluation of a Pain Management Manual for Hospice Providers to Support and Educate Family Caregivers

Abstract: Background: Family caregivers encounter many barriers to managing patients' pain in the home hospice setting. However, there are limited clinically applicable resources for hospice providers to help family caregivers identify and address these barriers. Aim: To develop a pain management manual for hospice providers to support family caregivers and conduct a preliminary providers' evaluation of the manual. Design and Participants: A pain management manual was developed and structured into 3 parts: (1) 5 common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…However, many hospice agencies have not developed adequate resources to prepare caregivers for symptom management. 2 While participants in our study reported little use of technology for patient/family education, they favored the use of telenovela video for family caregiver education and deliberation efforts.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…However, many hospice agencies have not developed adequate resources to prepare caregivers for symptom management. 2 While participants in our study reported little use of technology for patient/family education, they favored the use of telenovela video for family caregiver education and deliberation efforts.…”
Section: Discussionmentioning
confidence: 70%
“…Similarly, other studies have reported that the usefulness of videos depends on the preferences (printed vs web-based information) and personality of each person, 31 and the level of physical and psychological burden. 2 The telenovela evaluated in this study was developed systematically with a strong theoretical basis for future implementation in routine hospice care. Future interventions studies could consider using telenovela video as an intervention delivery tool and explore which caregiver and at what moment would be best to offer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations